2020
DOI: 10.3329/baj.v22i1.44944
|View full text |Cite
|
Sign up to set email alerts
|

Seed Harvesting at Different Maturity Stages of Siliqua on Seed Quality of Rapeseed-Mustard Varieties

Abstract: A laboratory experiment with three replicates was conducted at Plant Physiology Division research laboratory of Bangladesh Agricultural Research Institute (BARI) during November, 2015 to observe the seed quality of rapeseed-mustard by harvesting at different maturity stages of siliqua. Seeds were collected from siliqua of different rapeseed-mustard varieties and harvesting was made at different maturity stages based on their external color i.e., Green, pale yellow, Golden yellow and full maturity stage of sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Channaoui et al [22] similarly reported variable seed and seedling quality parameters of different rapeseed varieties in response to their genetical variation. Talukder et al [23] also observed same in some rapeseed-mustard varieties.…”
Section: Seed and Seedling Quality Parametersmentioning
confidence: 59%
“…Channaoui et al [22] similarly reported variable seed and seedling quality parameters of different rapeseed varieties in response to their genetical variation. Talukder et al [23] also observed same in some rapeseed-mustard varieties.…”
Section: Seed and Seedling Quality Parametersmentioning
confidence: 59%